X rays on quantum mechanics: Pauli Exclusion Principle and collapse models at test. (July 2015) - Curceanu, C; Bartalucci, S; Bassi, A; Bertolucci, S; Berucci, C; Bragadireanu, A M; Cargnelli, M; Clozza, A; De Paolis, L; Matteo, S Di; Donadi, S; d'Uffizi, A; et al.
Abstract: In the last decades huge theoretical effort was devoted to the development of consistent theoretical models, aiming to solve the so-called "measurement problem". Among these, the Dynamical Reduction Models possess the unique characteristic to be experimentally testable, thus enabling to set experimental upper bounds on the reduction rate parameter λ characterizing these models. By analysing the X-ray spectrum emitted by an isolated slab of Germanium, we set the most stringent limit on the λ parameter up to date.